Effect of carvedilol on arteriovenous graft primary patency. (December 2020) - Tseng, Yuan-Hsi; Liu, Chia-Yen; Lee, Chuan-Pin; Lin, Meng-Hung; Yang, Yao-Hsu
Background: The major mechanisms of arteriovenous graft (AVG) failure due to intimal hyperplasia (IH) are smooth muscle cell proliferation and inflammation. Therefore, carvedilol may improve AVG primary patency because of its anti-proliferative and anti-inflammatory activities. Methods: The data of end-stage renal disease patients receiving regular hemodialysis were collected from the National Health Insurance Research database. The end point was the first percutaneous transluminal angioplasty (PTA) for AVG failure or death during a follow-up period of two years or the end of 2013. The analysis was calculated with Cox proportional hazard model. Results: There were 3028 patients treated with carvedilol and 13, 704 patients not treated with carvedilol. According to a univariate analysis, the carvedilol group was younger, received more anti-hypertensive medications and platelet aggregation inhibitors, and had higher rates of diabetes mellitus and hyperlipidemia but had lower rates of hypotension and smoking. According to a multivariate analysis, after controlling for covariates, the use of carvedilol for more than 84 days reduced the probability of a first PTA for AVG failure by 9% compared with no use of carvedilol ( p = 0.021), but the use of carvedilol for 1 to 84 days did not. Conclusion: The results of this study indicate that the use of carvedilol for more than 84 days improves the primary patency of AVGs, but the use of carvedilol for less than 84 days does not.